Universal Expositions, physics-chemistry and new occupational diseases: the case of Marie Sklodowska Curie and radium girls - Salerno, Silvana (La Medicina del Lavoro, 2017)
Background: Radium discovery by Marie and Pierre Curies caused previously unknown diseases. Marie Sklodowska Curie (1867-1934) suffered from radiations effects, as did girls in the radium dial watches factories. Therapeutic effects of radium were soon discovered, its unhealthy effects were as yet unheard of. Objectives: Analysis of Marie Sklodowska Curie (Marie) and radium girls occupational exposure, taking scientific debate on radium dangerous effects into account. Methods: analysis of occupational exposure and diseases of Marie and radium girls in major documents, including Curie archive letters. Results: Marie had dermatitis, radiodermatitis, tinnitus, one abortion, cataracts, tubercolosis, aplastic anemia. She also was a victim of mobbing. Women employed in the New Jersey radium dial watches factories, often immigrants, died of jaw necrosis, sarcoma of femur, anemia, leukemia and other radium related diseases. Marie was first asked about radium adverse effects by the New Jersey Department of labour (1925), Lise Meitner (1928) and the American Society for Cancer Control (1929). In 1928 Alice Hamilton organized a radium conference in order to find a solution to the radium girls’ new disease. In 1929, during her second visit to the United States of America (USA), Marie declared how only prevention could save “radium girls”. In 1934 she died of aplastic anemia, just like many radium girls. That year International Labour Office listed the new disease as due to “radium, radioactive substances, X-rays”; it was followed in 1937 by five USA states. Conclusions: Unheard of knowledge, conflict of interest, scientific delay, incompetence and no prevention were yesterday, as they are today, the cause of many preventable women deaths.